Vaccine-related advertising in the Facebook Ad Archive. Issue 3 (16th January 2020) - Jamison, Amelia M.; Broniatowski, David A.; Dredze, Mark; Wood-Doughty, Zach; Khan, DureAden; Quinn, Sandra Crouse
Highlights: First assessment of vaccine-related advertisements on Facebook Ad Archive. Top pro-vaccine ad themes: vaccine promotion, philanthropy, news. Top anti-vaccine ad themes: vaccine harm, promoting choice, uncovering "fraud". Two buyers accounted for majority (54%) of anti-vaccine advertising content. Facebook policies negatively impact first time ad buyers, largely pro-vaccine. Abstract: Background: In 2018, Facebook introduced Ad Archive as a platform to improve transparency in advertisements related to politics and "issues of national importance." Vaccine-related Facebook advertising is publicly available for the first time. After measles outbreaks in the US brought renewed attention to the possible role of Facebook advertising in the spread of vaccine-related misinformation, Facebook announced steps to limit vaccine-related misinformation. This study serves as a baseline of advertising before new policies went into effect. Methods: Using the keyword 'vaccine', we searched Ad Archive on December 13, 2018 and again on February 22, 2019. We exported data for 505 advertisements. A team of annotators sorted advertisements by content: pro-vaccine, anti-vaccine, not relevant. We also conducted a thematic analysis of major advertising themes. We ran Mann-Whitney U tests to compare ad performance metrics. Results: 309 advertisements were included in analysis with 163 (53%) pro-vaccine advertisements and 145 (47%) anti-vaccine advertisements. Despite a similar number of advertisements, the median number of ads per buyer was significantly higher for anti-vaccine ads. First time buyers are less likely to complete disclosure information and risk ad removal. Thematically, anti-vaccine advertising messages are relatively uniform and emphasize vaccine harms (55%). In contrast, pro-vaccine advertisements come from a diverse set of buyers (83 unique) with varied goals including promoting vaccination (49%), vaccine related philanthropy (15%), and vaccine related policy (14%). Conclusions: A small set of anti-vaccine advertisement buyers have leveraged Facebook advertisements to reach targeted audiences. By deeming all vaccine-related content an issue of "national importance, " Facebook has further the politicized vaccines. The implementation of a blanket disclosure policy also limits which ads can successfully run on Facebook. Improving transparency and limiting misinformation should not be separate goals. Public health communication efforts should consider the potential impact on Facebook users' vaccine attitudes and behaviors.